2018
DOI: 10.5935/0004-2749.20180074
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological analysis of contact lens cases: impact of the hospital environment

Abstract: The types of bacteria contaminating the cases are generally not seen in eye diseases associated with contact lens use, suggesting that other decisive variables are involved in eye infection from a contaminated lens or case. Fungal contamination of contact lens cases appears to be an exception. Ridged cases are commonly used by contact lens wearers and present a potential risk to eye health. In addition, the results of bacterial tests between hospital workers and those who did not visit a hospital were not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Many variables were present in the study not allowing the exact type of bacteria to be identified. But more than 85% of the bacteria were gram-negative bacilli [36].…”
Section: Discussionmentioning
confidence: 99%
“…Many variables were present in the study not allowing the exact type of bacteria to be identified. But more than 85% of the bacteria were gram-negative bacilli [36].…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be owing to the higher rate of contact lens use (40.4%), which is a risk factor for gram-negative infections. 13,17…”
Section: Discussionmentioning
confidence: 99%
“…Guidance from professional bodies and solution manufacturers with respect to lens case maintenance may be contradictory [467]; lens case replacement advice varies between 1-3 months and few mention the need to rub and store cases face down. Further efforts to minimise case contamination may be achieved by use of non-ridged cases [468] and possibly cylindrical cases [469]. Promising outcomes in limiting biofilm formation have also been reported, through incorporation of various compounds into the materials of polypropylene contact lens cases [470][471][472], but additional testing is needed to establish their biocompatibility and safety.…”
Section: Cleaning Instructionmentioning
confidence: 99%